Analisis Pengaruh Pembangunan Objek Wisata Sungai Terhadap Pendapatan Masyarakat Lokal Dan Pedagang Tradisional. (Studi Pada Objek Wisata Manara Pandang Piere Tendean Banjarmasin) - Marliani, Gusti (Scientific : Jurnal Ilmu-Ilmu Sosial dan Ekonomi, 2017)
Effort to develop tourist objects to attract tourist visits careful planning basedon data and information available through research activities, the purpose of development of tourist attraction will be tailored to the expectations of tourists to the benefits of tourism services offered. Therefore, the attractions based on information research results will be more effective. One of the development of the Martapura riverbanks is the development of Siring Piere Tendean and the tower of view, the floating market, the procurement of river transportation, and the construction of the Bekantan statue as the mascot of South Kalimantan. The purpose of the development is the improvement of the economy of the community, both local communities and traditional traders around the development of these attractions so that this study aimsto know the influence of tourist attraction to the incomes of local communities andtraditional traders. This research is quantitative and analyzed descriptively. The data used are primary data taken from observation, documentation, questionnaire method.Sampling technique is using purposive sampling with data analysis technique using simple regression. The result of the research shows that the influence of tourism object development on the income of local community and traditional trader is R2 = 0,590 or59% after the development of Siring Piere Tandean. From the result it shows theincrease of income of local community and traditional trader.